The Effectiveness of Augmemted Reality and Flipped Classroom in Biology learning: A Meta-analysis - Oktarina, Karlini (eScience Humanity Journal, 2024)
This study aims to analyze the effectiveness of the use of Augmented Reality (AR) and the Flipped Classroom learning model in Biology learning through meta-analysis methods. Technology-based learning, such as AR, and flipped learning approaches (Flipped Classroom) are increasingly popular in science education, especially Biology, as they are both believed to improve concept understanding, student engagement, and learning outcomes. This meta-analysis was conducted by collecting and analyzing data from a variety of relevant empirical studies to assess the impact of the two models on students' academic achievement, conceptual comprehension, and critical thinking skills. The results of the meta-analysis showed that the use of AR and Flipped Classroom significantly improved students' understanding of Biology material and learning motivation compared to conventional learning methods with a value of d = 1,804 p< 0.001 high effect size category. Flipped Classroom is more effective in improving critical thinking skills, while AR makes a great contribution to the visualization and understanding of complex concepts. This study concludes that the integration of AR and Flipped Classroom in Biology learning has great potential to improve the quality of learning and student learning outcomes.